MITOS CANTIK PADA IKLAN PERAWATAN KULIT LANEIGE - Siti Novita Anindita, Rah Utami Nugrahani (ArtComm, 2018)
Beauty is identical with women. Beautiful has many versions depending on several factors, point of view, until the area. Laneige skincare advertisement shows signs and symbols that indicate a beautiful element. This ad uses YouTube social media which is new media. YouTube has audio-visual features and YouTube is the most popular online video community in the world. The author wants to see the beautiful myths that existed in the Laneige skin-care ad version of "Waterbank Series" in semiotics using Roland Barthes's semiology. This research uses a constructivist-descriptive paradigm with Roland Barthes Semiotics analysis technique which has three elements: the first level meaning (denotation), the second level meaning (connotation), and the myth. The results of this study are advertising shows that the standard of beauty in accordance with a beauty standard of Korea where has a bright white skin, long hair, a pointed nose and sharp chin, slim body and slim waist. This research confirms that the portrayal of models in advertisements shows the beauty myth in Korean standard of beauty. Keywords: Semiotics, Beauty Myth, YouTube Ad